The Effect of Work Quality and Work Professionalism on Employee Performance at PT Non Ferindo Utama - Bezisokhi Laia; Karnawi Kamar; Masduki Asbari (Faculty of Science and Technology University of Pramita Indonesia, 2022)
PT Non Ferindo Utama is a manufacturing company engaged in the industry that serves and sells pure tin. This study aims to answer questions about the effect of work quality and work professionalism partially or simultaneously on employee performance at PT Non Ferindo Utama. The research methodology used is a quantitative method. The population in this study were employees of the production of PT Non Ferindo Utama. The sampling technique in this study is probability sampling with simple random sampling. The sample in this study amounted to 32 respondents who are production employees. The data collection technique used questionnaire data which was processed using the SPSS program. Data analysis used multiple linear regression. The results showed that there was a partial effect of work quality variables, as well as work professionalism on the performance of PT Non Ferindo Utama employees. Simultaneously, the variables of work quality and work professionalism also affect the performance of PT Non Ferindo Utama employees. Due to the influence of work quality and work professionalism both partially and simultaneously on employee performance, PT Non Ferindo Utama needs to pay more attention to the quality of work on employees and work professionalism in the organization to improve employee performance as expected by the company.